Biogeochemical data and chlorophyll a concentrations of phytoplankton during a cruise of the 53rd Japanese Antarctic Research Expedition in the austral summer of 2011-2012 - Takahashi, Kunio T.; Iida, Takahiro; Nishioka, Jun; Odate, Tsuneo (国立極地研究所, 2014)
departmental bulletin paper